The Joys of Initiating Laparoscopic Surgery in a Small Rural Hospital - Havin, Dianna; Frayne, Patricia (Operating Room Nurses Association of Canada Journal, 1993)
It all started with a phone call from our surgical supply representative regarding an upcoming seminar on laparoscopic cholecystectomy.